INSTRUCTIONAL STRATEGIES: INTEGRATING FAITH AND LEARNING IN TERTIARY EDUCATION - Alvyn Hendriks (Fakultas Filsafat Universitas Advent Indonesia, 2019)
Despite the vast research on the integration of faith and learning (IFL), littleis known on how instructional strategies can enhance what true educationnecessitates—an IFL that prepares learners beyond the present life. This studyexplores the impact of instructional strategies towards IFL. It reveals that to be moreeffective and powerful in such integration, instructional strategies play an importantrole—within and without the classroom setting.